Designing reopening strategies in the aftermath of COVID-19 lockdowns: Some principles with an application to Denmark - Torben M. Andersen; Philipp J. H. Schröder; Michael Svarer (Institute of Labor Economics (IZA), 2020)
Governments across the globe have responded to the threat of the Covid-19 virus by imposing substantial lockdown measures largely guided by epidemiological concerns. These lockdowns come at significant economic costs with increased risk of e.g. mass unemployment. Recently, debates have emerged on how to design reopening strategies that achieve the largest possible economic gains while constraining the spread of the virus. The present paper identifies five central challenges economists face in delineating the trade-off between containing the virus from spreading and the economic consequences and costs of lockdown measures. While the principle of tradeoffs is at the core of economics, the road to actually operationalizing this perspective on Covid-19-related lockdown measures is still unpaved. We present several workarounds to the identified challenges based on a recently prepared economic expert assessment commissioned by the Danish government. A reduced form indicator for virus spread pressure is developed and mapped against economic indicators. The resulting tool captures the trade-off between health and economic concerns and can guide the design of reopening strategies.
Keywords: A1; H3; 330; COVID-19; reopening strategies; fiscal response